Land development and improved water management: the Smart-Valleys approach in Ivory Coast - CGIAR Research Program on Rice (2021)
The Smart-Valleys approach has been successfully piloted in Cote d’Ivoire. Overall, the Smart-Valleys approach increased soil moisture by 53% and reduced weed biomass by 20%. Rice yield was increased by 37% and the yield gap was reduced by 23% compared to the non-developed site.